2016
DOI: 10.2174/1874834101609010236
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Self-aggregating Proppants: New Approaches to Proppant Flowback Control

Abstract: Due to the high rate of proppant flowback after hydraulic fracturing stimulations, surface modified quartz sand proppants with excellent proppant flowback control abilities, self-aggregating proppants, were prepared. These surface modified proppants can aggregate together spontaneously and form a proppant column in water based liquid environment. Analyses show that the strong hydrogen bonds contribute to the absorption of the surface modifier onto the proppants, and the softening effect of the water to the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A large volume of proppants is pumped into the formation to enhance transportation of shale gas from the formation to the wellbore in commercial quantities. Such production requires the complex network of artificial fractures to have sufficient conductivity to sustain the whole period of production . Unfortunately, the techniques for transporting and placing proppants in the formation to hold the fractures exhibit formation damage near the fracture surface that affects fracture packing. Many mechanisms impair the fracture conductivity during the process of fracturing. ,, These include proppant embedment, closure stress effect, , proppant crushing, , cyclic stress, fine migration, proppant pack diagenesis, , and the blockage caused by the gel residue in the proppant pack and gel filter cake at the fracture face. , …”
Section: Application Of Nanotechnology For Formation Damage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A large volume of proppants is pumped into the formation to enhance transportation of shale gas from the formation to the wellbore in commercial quantities. Such production requires the complex network of artificial fractures to have sufficient conductivity to sustain the whole period of production . Unfortunately, the techniques for transporting and placing proppants in the formation to hold the fractures exhibit formation damage near the fracture surface that affects fracture packing. Many mechanisms impair the fracture conductivity during the process of fracturing. ,, These include proppant embedment, closure stress effect, , proppant crushing, , cyclic stress, fine migration, proppant pack diagenesis, , and the blockage caused by the gel residue in the proppant pack and gel filter cake at the fracture face. , …”
Section: Application Of Nanotechnology For Formation Damage Controlmentioning
confidence: 99%
“…146−148 Many mechanisms impair the fracture conductivity during the process of fracturing. 145,148,149 These include proppant embedment, 150 closure stress effect, 151,152 proppant crushing, 153,154 cyclic stress, 148 fine migration, 155 proppant pack diagenesis, 156,157 and the blockage caused by the gel residue in the proppant pack and gel filter cake at the fracture face. 158,159 Recent studies have demonstrated that the use of nanoparticles can improve and control formation damage during stimulation 8 compared to conventional methods.…”
Section: Wettability Alterationmentioning
confidence: 99%